A Combination of Cabozantinib and Radiation Does Not Lead to an Improved Growth Control of Tumors in a Preclinical 4T1 Breast Cancer Model - Reppingen, Norman; Helm, Alexander; Doleschal, Laura; Durante, Marco; Fournier, Claudia (Frontiers in Oncology, 2021)
The tyrosine kinase inhibitor Cabozantinib has been applied in clinical studies in combination with radiotherapy. We investigated the effect of such combination on triple-negative 4T1 cells as a metastatic breast cancer model in vitro and in vivo upon inoculation in BALB/c mice. In vitro assays indicated a potential for improved effects using the combination. Both Cabozantinib (2.5 µM) and 10 Gy of 250 kV x-rays were able to cease the growth of 4T1 cells as revealed by growth curves. In a clonogenic survival assay, the effect of Cabozantinib added on the effects of irradiation and the effectiveness of inhibiting the clonogenic survival was found to be 2 (RBE10). Additionally, cell death measurements of apoptosis plus necrosis revealed a synergistic effect when combining irradiation with Cabozantinib. Surprisingly, however, in vivo tumor growth kinetics showed no additional effect in growth control when irradiation was used together with Cabozantinib. Since both ionizing radiation and Cabozantinib are acknowledged to feature immunogenic effects, we additionally investigated the effect of the treatments on lung metastases. No difference to the control groups was found here, neither for irradiation nor Cabozantinib alone nor in combination. Yet, upon analysis of the mice’ livers, CD11b-positive cells, indicating immune suppressive myeloid derived suppressor cells were found diminished following treatment with Cabozantinib. In conclusion, despite promising in vitro controls of the combination of Cabozantinib and irradiation, tumor growth control was not increased by the combination, which was true also for the occurrence of lung metastases.